Determinants and implications of the growing scale of livestock farms in four fast-growing developing countries - Delgado, Christopher L.; Narrod, Clare; Tiongco, Marites; Barros, Geraldo Sant'Ana de Camargo; Catelo, Maria Angeles O.; Costales, Achilles; Mehta, Rajesh; Naranong, Viroj; Poapongsakorn, Nipon; Sharma, Vijay Paul; de Zen, Sergio (International Food Policy Research Institute, 2008)
The rapid growth in consumer demand for livestock offers an opportunity to reduce poverty among smallholder livestock farmers in the developing world. These farmers' opportunity may be threatened, however, by competition from larger-scale farms. This report assesses the potential threat, examining various forms of livestock production in Brazil, India, the Philippines, and Thailand. Findings show that the competitiveness of smallholder farms depends on the opportunity cost of family labor and farmers' ability to overcome barriers to the acquisition of production- and market-related information and assets. Pro-poor livestock development depends, therefore, on the strengthening of institutions that will help smallholders overcome the disproportionately high transaction costs in securing quality inputs and obtaining market recognition for quality outputs. These and other findings make this report a useful guide for researchers and others concerned with the opportunities and risks of smallholder livestock farming.